Pengaruh Pengendalian Persediaan Terhadap Kinerja Departemen Penjualan Pada Depo Jaya Bangunan - Putri, Audiska Marshanda Retno; Animah, Animah; Astuti, Widia (Akbis: Media Riset Akuntansi dan Bisnis, 2023)
This study was conducted to examine the effect of inventory control on sales department performance. The research was conducted at the building's Jaya depot. There are 64 research samples selected through purposive sampling technique. Data analysis procedures used to test the validity, reliability test and hypothesis testing. The data analysis tool used in this study is Partial Least Square (PLS) version 3.0. The results showed that inventory control had a significant and positive effect on sales department performance. Inventory controls are used to prevent theft, fraud, and damage. Efforts to monitor and find out the goals of a company have been achieved, namely through controlling merchandise inventory. The efficiency of the internal control system can be further improved by recording and supervising all activities within the company and ensuring that this efficiency can improve company performance. Warehouse management systems can reduce errors in picking goods, assist in stock control, increase work productivity, and improve warehouse security